Effects of silica on the formation of epoxidised natural rubber/polyvinyl chloride membrane - Nazwa Jon; Ibrahim Abdullah; Rizafizah Othaman (Universiti Kebangsaan Malaysia, 2013)
The presence of pores plays an important role for many membrane processes especially in ultrafiltration and microfiltration. Epoxidised natural rubber (ENR)/polyvinyl chloride (PVC) membranes filled with two types of silica fillers were prepared via simultaneous solvent exchange and evaporation of solvent technique. Two types of silica, i.e. microsilica (microcrystalline silica powder) and nanosilica (generated from tetraethoxysilane (TEOS)) were used. The chemical composition, morphology and mechanical stability of the membranes were studied. Both types of silica showed good interaction with the membrane matrix. The formation of pores depended on the size of silica particles added. Microsilica produced large pores while in-situ generated nanosilica produced nanosized pores. The mechanical properties of membrane improved with the addition of silica. The tensile strength increased from 10.6 MPa to 17.8 MPa and 14.5 MPa for nanosilica and microsilica filled membrane while the tensile modulus increased from 1.6 MPa to 3.8 MPa and 3.4 MPa, respectively. Thus, both types of silica acted as a filler as well as pore forming agent for the ENR/PVC membrane.